Role of procalcitonin in bacteremic patients and its potential use in predicting infection etiology. Issue 2 (1st February 2019) - Bassetti, Matteo; Russo, Alessandro; Righi, Elda; Dolso, Elisabetta; Merelli, Maria; D'Aurizio, Federica; Sartor, Assunta; Curcio, Francesco
ABSTRACT: Introduction : Bloodstream infections (BSI) and their evolution to sepsis or septic shock are one of the most important causes of morbidity and mortality; for this reason, arapid recognition and diagnosis of these infections are crucial to improve patients' outcome. Area covered : Procalcitonin (PCT) is considered an important biomarker for diagnosis of infection, routinely used to identify patients developing severe bacterial infections. In this scenario, management of BSI is complicated by the increasing rate of multidrug-resistantstrains, and an early recognition of severe infections is mandatory. Moreover, an appropriate use and prescription of antibiotics is important to reduce the risk of development of further antibiotic resistances. Expert opinion : we reviewed recent literature about the use of PCT in bacteremic patients to determine its role to predict infections, severity of clinical condition and antibiotic therapy duration; its role was defined in many studies to reduce duration of antibiotic treatment, especially in critically ill patients and for lower respiratory tract infections. Moreover, we reported recent studies in which PCT showed ahigh performance to detect precociously infections due to Gram-negativestrains. Data from the literature confirm that PCT should not be used as astand-alonetest in the absence of clinical judgment.